(untitled) (Research, Society and Development, 2022)
This systematic review was due to the problem: Are companion animals good experimental models for the study of melanoma and squamous cell carcinomas in humans? The data search was carried out by electronic means, with scientific articles published between the years 2016 to 2021, in Portuguese, Spanish and English. The databases used were: Medical literature Analysis and Retrivial System Online via MEDLINE (PubMed) and Scientific Electronic Library Oline (SciELO). Descriptors used: basal cell carcinoma, melanoma, squamous cell carcinoma. The search strategy was (basal cell carcinoma OR melanoma OR squamous cell carcinoma) AND (dog OR cat) AND (human) in PUBMED and (basal cell carcinoma OR melanoma OR squamous cell carcinoma) AND (dog OR cat) AND (human) on the Scielo platform. Eleven original works were selected, published in the period determined in the methodology. The studies originated in Italy, the United States of America, the United Kingdom, France, Switzerland, Japan and Brazil, all in English. Melanoma was the target of 81.8% of the studies and squamous cell carcinoma, 18.2%. No studies have addressed Basal Cell Carcinoma. With this study, it is concluded that dogs and cats are excellent models for comparative oncology, especially as they are large animals with immunocompetent characteristics, sharing the same environment as humans. They develop neoplasms in a relatively shorter time when compared to humans, demonstrating genetic, molecular, epidemiological and histopathological similarities, with the potential to benefit both species in the development of new therapies and improvement of existing therapies.